GAMA, José Basílio da. As Minas de Ouro do Brasil. Brasilienses Aurifodinae. Tradução e organização Alexandra de Brito Mariano. São Paulo: Edusp, 2024. - Leite, Leni Ribeiro (Classica - Revista Brasileira de Estudos Clássicos, 2024)
This is a review of the recent publication of As Minas de Ouro do Brasil. Brasilienses Aurifodinae, with translation by Alexandra de Brito Mariano.